Kelebihan dan Kekurangan Teknologi Hidrogen sebagai Energi Terbarukan yang Ramah Lingkungan - Bagustianto Adipati; M. Fikri Adrian; Adnan Kurniawan; Rahmat Riski; Tri Prasetia Utama (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The global energy transition necessitates the development of sustainable and low-emission energy systems, positioning hydrogen as a strategic energy carrier with significant potential. This study aims to critically evaluate the advantages and limitations of hydrogen technology as an environmentally friendly renewable energy source through a systematic qualitative synthesis approach. The findings indicate that hydrogen offers key advantages, including high energy density by mass, operational zero-emission characteristics, and flexibility in production from diverse renewable sources. However, these strengths are constrained by systemic challenges such as low energy conversion efficiency, complex and costly infrastructure for storage and distribution, and environmental impacts that depend heavily on production pathways. Lifecycle-based analysis reveals that hydrogen’s sustainability is conditional upon the use of renewable energy inputs. Furthermore, policy frameworks, green financing mechanisms, and technological innovations in materials and catalysis are essential to enhance feasibility and scalability. The study concludes that hydrogen should be positioned as a complementary component within integrated energy systems, requiring multidimensional evaluation to support effective and evidence-based energy transition strategies.